The millionaire friend-to-friend fundraising. (5th October 2022) - Vasconcellos, Luis Henrique Rigato; Biazzin, Cristiane; Ferreira, Fernando Coelho Martins; Oliveira, Alexandre Vasserman de
The case portrays a real dilemma experienced by Alexandre, founder of the fourth largest Brazilian social mobilisation movement for health called VemPraGuerra He joined efforts with his brother and a friend (both resident doctors) to structure a project during the first half of 2020. Amid the COVID-19 medical supplies shortage, they were able to gather R$6 million (about US$1.2 million at that time). This funding was summoned to assist Hospital das Clinicas de Sao Paulo, the largest Brazilian health complex. The case study contributes to the currently scarce body of knowledge devoted to teaching stakeholder theory. It is an applied example of social entrepreneurship, the promotion of social change, and the contemporaneity of the COVID-19 pandemic.